Vitamin E nanocapsule and preparation method thereof
By using non-toxic emulsifiers such as sugar-based surfactants and glycerol, combined with cocamidopropyl betaine and zein, vitamin E nanocapsules are prepared by spray drying technology, which solves the problems of irritability and complex and high preparation of surfactants in the prior art, and achieves safe, efficient and low-cost nanocapsules preparation.
Patent Information
- Application Number
- CN202510139182.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-11
AI Technical Summary
The surfactants used in the preparation process of existing vitamin E nanocapsules are irritating to the skin, and the preparation method of food-based surfactants is complex and costly.
Vitamin E nanocapsules were prepared using non-toxic and harmless sugar-based surfactant and glycerol as emulsifiers and cosurfactants, combined with cocamidopropyl betaine and zein using spray drying technology.
The particle size and PDI of the nanocapsules are reduced, the safety and storage stability of the product are improved, the preparation process is simplified and the production cost is reduced.
Smart Images

Figure BDA0005264238680000081 
Figure BDA0005264238680000091 
Figure BDA0005264238680000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocapsule preparation, and in particular to a vitamin E nanocapsule and a preparation method thereof. Background Art
[0002] Vitamin E is a type of essential nutrient for the human body. It is a type of highly effective and safe natural antioxidant. It is a strong and effective free radical scavenger that can protect the body's cell membranes and macromolecules from free radical attacks. It has good effects in preventing and treating cardiovascular diseases, anti-tumor, enhancing human immune function, and delaying aging. Vitamin E is an oil-soluble, heat-sensitive substance that is difficult to mix with water-soluble substances, making it difficult to evenly add to water-soluble products. In addition, ultraviolet rays, alkalis, and oxygen can destroy vitamin E, so it is usually sealed and stored away from light, which greatly limits the application of vitamin E in the fields of food and cosmetics. During use, vitamin E is usually nano-encapsulated to overcome its shortcomings of being insoluble in water and easy to oxidize and decompose.
[0003] At present, most of the research on vitamin E nanocapsules uses traditional surfactants, such as sodium lauryl ether sulfate, which often makes the product irritating. The use of food-based surfactants, such as Tween-80, has a complicated preparation process and high production costs. In the research on vitamin E nanocapsules using new wall materials (such as polycaprolactone, lactate, etc.), although the vitamin E encapsulation efficiency is high, the toxic organic solvent acetone is used, which does not meet the requirements of green chemistry and environmental sustainability. In order to prepare green and safe nanocapsules, the selection of wall materials and emulsifiers is very important. These factors affect the production cost, the dispersion degree of the core material, and the encapsulation efficiency.
[0004] Therefore, how to disclose a vitamin E nanocapsule that has little skin irritation, a simple preparation method, and a pollution-free preparation process is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0005] The purpose of the present invention is to provide a vitamin E nanocapsule and a preparation method thereof, so as to solve the problem that the surfactant used in the preparation process of the existing vitamin E nanocapsule is irritating to the skin, and the preparation method using a food-based surfactant is complicated and costly.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a vitamin E nanocapsule, which is made from the following raw materials in parts by weight:
[0008] 5-20 parts of vitamin E, 10-30 parts of cosurfactant, 10-30 parts of sugar-based surfactant, 3-8 parts of cocamidopropyl betaine, 5-20 parts of zein, 15-50 parts of outer wall material, 100-115 parts of ethanol solution, and 200-230 parts of water;
[0009] The sugar-based surfactant comprises one or more of alkyl glycoside, alcohol ether glycoside, alkyl glycoside sulfosuccinate and sucrose ester.
[0010] Preferably, the co-surfactant is glycerol.
[0011] Preferably, the outer wall material includes one or more of sodium alginate, sodium carboxymethyl cellulose, sodium hydroxyethyl cellulose, sodium hydroxypropyl cellulose, xanthan gum and pectin;
[0012] The concentration of the ethanol solution is 70-90%.
[0013] The present invention also provides a method for preparing the above-mentioned vitamin E nanocapsules, comprising the following steps:
[0014] 1) mixing vitamin E, a cosurfactant, a sugar-based surfactant, zein, and an ethanol solution to obtain a phase A;
[0015] Mix the outer wall material, cocamidopropyl betaine and water to obtain phase B;
[0016] 2) Mixing phase B with phase A and drying to obtain vitamin E nanocapsules.
[0017] Preferably, the drying method in step 2) is spray drying, and the drying time is 2 to 3 hours.
[0018] The present invention has at least the following beneficial effects:
[0019] (1) In the preparation process of vitamin E nanocapsules, non-toxic and harmless sugar-based surfactants are used as emulsifiers, which are safer.
[0020] (2) Using glycerol as a cosurfactant and cocamidopropyl betaine as a coemulsifier, the oil-water interfacial tension was reduced, thereby reducing the particle size and PDI of the nanocapsules.
[0021] (3) The particle size of the nanocapsules is small and the storage stability is high. The particle size distribution of the vitamin E nanocapsules finally prepared is in the range of 150 to 300 nm, and the PDI (polymer dispersity index) is less than 0.3.
[0022] (4) The preparation process is simple, the production cost is low, and it is easy to apply to industrial production. DETAILED DESCRIPTION
[0023] The present invention provides a vitamin E nanocapsule, which is made from the following raw materials in parts by weight:
[0024] 5-20 parts of vitamin E, 10-30 parts of cosurfactant, 10-30 parts of sugar-based surfactant, 3-8 parts of cocamidopropyl betaine, 5-20 parts of zein, 15-50 parts of outer wall material, 100-115 parts of ethanol solution, 200-230 parts of water, preferably vitamin E 6-18 parts, cosurfactant 12-28 parts, sugar-based surfactant 12-28 parts, cocamidopropyl betaine 4-7 parts, zein 6-18 parts, outer wall material 20-40 parts, ethanol solution 103-112 parts, water 205-225 parts, more preferably vitamin E 10-15 parts, cosurfactant 15-25 parts, sugar-based surfactant 15-25 parts, cocamidopropyl betaine 5-6 parts, zein 8-15 parts, outer wall material 25-35 parts, ethanol solution 105-110 parts, water 210-220 parts.
[0025] The sugar-based surfactant comprises one or more of alkyl glycoside, alcohol ether glycoside, alkyl glycoside sulfosuccinate and sucrose ester.
[0026] In the present invention, the co-surfactant is glycerol.
[0027] In the present invention, the preparation method of the alkyl glycoside sulfosuccinate is as follows:
[0028] In a 250mL round-bottom four-necked flask equipped with a thermometer, a mechanical stirrer and a reflux condenser, add alkyl glycoside and maleic anhydride in a molar ratio of 1:1.05, then add 10mL of squalane (as a dispersant), pass nitrogen, and carry out esterification reaction at 90°C for 2h. Then cool the mixture to room temperature and let it stand overnight to separate squalane. The intermediate is obtained as a light yellow liquid. Then 75mL of sodium sulfite solution (20%, w / %) is added to the intermediate, and stirring is continued at 50°C for 2h under a nitrogen atmosphere to obtain alkyl glycoside sulfosuccinate.
[0029] In the present invention, the outer wall material includes one or more of sodium alginate, sodium carboxymethyl cellulose, sodium hydroxyethyl cellulose, sodium hydroxypropyl cellulose, xanthan gum and pectin;
[0030] The concentration of the ethanol solution is 70-90%.
[0031] The present invention also provides a method for preparing the above-mentioned vitamin E nanocapsules, comprising the following steps:
[0032] 1) mixing vitamin E, a cosurfactant, a sugar-based surfactant, zein, and an ethanol solution to obtain a phase A;
[0033] Mix the outer wall material, cocamidopropyl betaine and water to obtain phase B;
[0034] 2) Mixing phase B with phase A and drying to obtain vitamin E nanocapsules.
[0035] In the present invention, the drying method in step 2) is spray drying, and the drying time is 2 to 3 hours.
[0036] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0037] Example 1
[0038] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside (Shanghai Fakai Chemical Co., Ltd., APG1214), 15 parts of zein (Shaanxi Dennis Biotechnology Co., Ltd., DNS-2023030902), and 110 parts of 75% ethanol solution were mixed and magnetically stirred for 1.5 h to obtain phase A.
[0039] (2) Mix 30 parts of sodium alginate, 5 parts of cocamidopropyl betaine (Yunbang Biotechnology, YB15392) and 210 parts of water, and stir magnetically for 1.5 hours to obtain phase B.
[0040] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0041] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0042] The measured average particle size of the vitamin E nanocapsules was 205.75 nm, the PDI was 0.136, and the potential was -55.58 mV.
[0043] Example 2
[0044] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of sucrose ester (SE-3, Hangzhou Ruilin Chemical Co., Ltd.), 10 parts of zein, and 110 parts of 80% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0045] (2) 30 parts of sodium carboxymethyl cellulose, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0046] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0047] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0048] The measured average particle size of the vitamin E nanocapsules was 196.06 nm, the PDI was 0.235, and the potential was -72.48 mV.
[0049] Example 3
[0050] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside sulfosuccinate, 17 parts of zein, and 110 parts of 83% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0051] (2) 30 parts of a mixture of sodium hydroxyethyl cellulose and sodium hydroxypropyl cellulose (mass ratio of 1:1), 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0052] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0053] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0054] The measured average particle size of vitamin E nanocapsules is 192.33 nm, the PDI is 0.168, and the potential is -84.36 mV.
[0055] Example 4
[0056] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alcohol ether glycoside (Jiangsu Wanqi Biotechnology Co., Ltd., product number: AEG-300), 6 parts of zein, and 110 parts of 85% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0057] (2) 30 parts of sodium hydroxyethylcellulose, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0058] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0059] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0060] The measured average particle size of vitamin E nanocapsules was 187.06 nm, the PDI was 0.178, and the potential was -75.69 mV.
[0061] Example 5
[0062] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside sulfosuccinate, 18 parts of zein, and 110 parts of 78% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0063] (2) sodium hydroxypropylcellulose, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0064] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0065] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0066] The measured average particle size of the vitamin E nanocapsules was 215.35 nm, the PDI was 0.173, and the potential was -63.86 mV.
[0067] Example 6
[0068] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside, 12 parts of zein, and 110 parts of 82% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0069] (2) 30 parts of xanthan gum, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0070] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0071] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0072] The measured average particle size of the vitamin E nanocapsules was 197.26 nm, the PDI was 0.136, and the potential was -42.55 mV.
[0073] Example 7
[0074] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alcohol ether glycoside, 16 parts of zein, and 110 parts of 76% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0075] (2) 30 parts of pectin, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0076] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0077] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0078] The measured average particle size of the vitamin E nanocapsules was 216.97 nm, the PDI was 0.218, and the potential was -39.99 mV.
[0079] Comparative Example 1
[0080] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 10 parts of zein, and 110 parts of 75% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0081] (2) 30 parts of sodium alginate, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0082] Compared with the examples, in Comparative Example 1, no sugar-based surfactant was added, phase A was stratified and unstable, and microcapsules could not be prepared.
[0083] Comparative Example 2
[0084] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside, 3 parts of zein, and 110 parts of 80% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0085] (2) 30 parts of sodium carboxymethyl cellulose, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0086] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0087] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0088] Compared with the example, the comparative example 2 added less zein, the prepared product had poor stability and was unstable, and the vitamin E was easy to leak.
[0089] Comparative Example 3
[0090] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alcohol ether glycoside, 30 parts of zein, and 110 parts of 83% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0091] (2) 30 parts of a mixture of sodium hydroxyethyl cellulose and sodium hydroxypropyl cellulose (mass ratio of 1:1), 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0092] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a suspension.
[0093] (4) Dry the mixture using a spray dryer for 2.5 h to obtain a powder.
[0094] Compared with the examples, in comparative example 3, too much zein was added, and the prepared product had high viscosity, poor stability, was unstable, and vitamin E was easy to leak.
[0095] Comparative Example 4
[0096] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of sucrose ester, 6 parts of zein, and 110 parts of 85% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0097] (2) 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0098] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a vitamin E nanocapsule suspension.
[0099] (4) Use a spray dryer to dry for 2.5 hours to obtain nanocapsule powder.
[0100] Compared with the embodiment, the outer wall material was not added in comparative example 4, and the prepared product had high viscosity, poor stability, instability, and vitamin E was easy to leak.
[0101] Comparative Example 5
[0102] (1) 30 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alkyl glycoside sulfosuccinate, 3 parts of zein, and 110 parts of 78% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0103] (2) 30 parts of sodium hydroxypropyl cellulose, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0104] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a suspension.
[0105] (4) The sample was dried using a spray dryer for 2.5 h.
[0106] Compared with the examples, too much vitamin E was added in comparative example 5, and vitamin E nanocapsules could not be prepared.
[0107] Comparative Example 6
[0108] (1) 15 parts of vitamin E, 25 parts of co-surfactant glycerol, 20 parts of alcohol ether glycoside, 12 parts of zein, and 110 parts of 50% ethanol solution were mixed and magnetically stirred for 1.5 hours to obtain phase A;
[0109] (2) 30 parts of xanthan gum, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed and magnetically stirred for 1.5 hours to obtain phase B;
[0110] (3) Add phase B into phase A and stir magnetically for 1 h to obtain a suspension.
[0111] (4) Dry the mixture using a spray dryer for 2.5 h to obtain a powder.
[0112] Compared with the examples, the concentration of the ethanol solution added in Comparative Example 6 was too low, the solubility of zein was poor, and vitamin E microcapsules could not be prepared.
[0113] Comparative Example 7
[0114] (1) 15 parts of vitamin E, 25 parts of cosurfactant glycerol, 20 parts of alkyl glucoside, 16 parts of zein, 110 parts of 76% ethanol solution, 30 parts of pectin, 5 parts of cocamidopropyl betaine and 210 parts of water were mixed.
[0115] (2) The mixture was magnetically stirred for 1 h to obtain a suspension.
[0116] (4) Dry the mixture using a spray dryer for 2.5 h to obtain dry powder.
[0117] Compared with the examples, comparative example 7 adopts a one-step method to directly mix all raw materials, and vitamin E microcapsules cannot be prepared.
[0118] The test results of the vitamin E nanocapsules obtained in Examples 1 to 7 and Comparative Examples 1 to 7 are shown in Table 1. Table 1 Test results of the microbial E nanocapsules obtained in Examples and Comparative Examples
[0119]
[0120]
[0121]
[0122] As can be seen from the above embodiments, the present invention provides a vitamin E nanocapsule and a preparation method thereof. As can be seen from Table 1, the prepared products are non-irritating. Comparative Example 1 does not add a sugar-based surfactant, and the A phase is stratified and unstable, so microcapsules cannot be prepared; Comparative Example 2 adds less zein, and the prepared product has poor stability and is unstable, and vitamin E is easy to leak; Comparative Example 3 adds more zein, and the prepared product has poor stability and is unstable, and vitamin E is easy to leak; Comparative Example 4 does not add an outer wall material, and the prepared product has a large viscosity, poor stability, and is unstable, and vitamin E is easy to leak; Comparative Example 5 adds too much vitamin E, and vitamin E nanocapsules cannot be prepared; Comparative Example 6 adds an ethanol solution with too low a concentration, and zein has poor solubility, so vitamin E microcapsules cannot be prepared; Comparative Example 7 changes the preparation method, and vitamin E nanocapsules cannot be prepared. Examples 1 to 7 are all within the scope of the present invention, and the prepared nanocapsules have small particle sizes and high storage stability; the preparation process conditions are simple, the production cost is low, and they are easy to apply to industrial production.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A vitamin E nanocapsule, characterized in that: Made from the following raw materials in parts by weight: 5-20 parts of vitamin E, 10-30 parts of cosurfactant, 10-30 parts of sugar-based surfactant, 3-8 parts of cocamidopropyl betaine, 5-20 parts of zein, 15-50 parts of outer wall material, 100-115 parts of ethanol solution, and 200-230 parts of water; The sugar-based surfactant comprises one or more of alkyl glycoside, alcohol ether glycoside, alkyl glycoside sulfosuccinate and sucrose ester.
2. A vitamin E nanocapsule according to claim 1, characterized in that: The co-surfactant is glycerol.
3. A vitamin E nanocapsule according to claim 2, characterized in that: The outer wall material includes one or more of sodium alginate, sodium carboxymethyl cellulose, sodium hydroxyethyl cellulose, sodium hydroxypropyl cellulose, xanthan gum and pectin; The concentration of the ethanol solution is 70-90%.
4. The method for preparing a vitamin E nanocapsule according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) mixing vitamin E, a cosurfactant, a sugar-based surfactant, zein, and an ethanol solution to obtain a phase A; Mix the outer wall material, cocamidopropyl betaine and water to obtain phase B; 2) Mixing phase B with phase A and drying to obtain vitamin E nanocapsules.
5. The method for preparing vitamin E nanocapsules according to claim 4, characterized in that: The drying method in step 2) is spray drying, and the drying time is 2 to 3 hours.